Efektivitas Penerapan Edmodo Di SD Labschool UNNES - Adi Mashudi; Azalea Dwi Rahmatika (PGSD Universitas Muhammadiyah Cirebon, 2020)
The development of the current age has been very concerned with Information and Communication Technology (ICT) when learning at the elementary level now has to use internet technology as the times. Today's students are Generation Z who are able to use internet access as they wish. One of them is learning to use Edmodo Application as a learning resource that is up to date and develops students' ability towards technology. The purpose of this study was to determine the effectiveness of Edmodo implementation and describe what had been done by UNNES Labschool Elementary School, the subjects of this study were teachers and students of UNNES Elementary School Labs. Data taken from elementary school teacher's observation and interviews. Based on data analysis, the results of edmodo have long been applied which provide active learning activities both online and face to face. Keywords: Effectiveness, Edmodo, UNNES Labschool For Elementary School